Out-of-plane transient thermal conductivity measurements for bulk semiconducting conjugated polymers using fast scanning calorimetry - Zhao, Haoyu; Prine, Nathaniel; Ma, Guorong; Zhang, Yongcao; Haque, Md Azimul; Baran, Derya; Gu, Xiaodan (Sustainable energy & fuels, 2023)
Thermal conductivity directly impacts the performance of organic thermoelectric devices which convert heat into useful electricity. However, quantitatively measuring the bulk thermal conductivity of conjugated polymers remains complicated and hinders the rational design of advanced organic thermoelectric materials and true key performance calculation, figure of merit ( ZT ). The novel fast scanning calorimetry is adopted to address these limitations for the first time by measuring the heat conduction for conjugated polymeric films. Out of plane thermal conductivity of polydiketopyrrolopyrrole (PDPPT) based polymers and poly (3-hexylthiophene) (P3HT) films are quantitatively captured by directly monitoring heat transfer through tens of micrometer thick polymer films. For undoped polymers, PDPPT displayed a higher out of plane thermal conductivity than P3HT (0.263 vs. 0.168 W m −1 K −1 ) due to higher backbone rigidity. After doping with 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ), the thermal conductivity of doped PDPPT first increases at lower doping levels up to 5 wt%, and then decreases at higher doping levels, which can be attributed to changes in the degree of crystallinity for doped films quantified by X-ray scattering measurements. The highest thermal conductivities are found for doping levels ranging from of 2.5% for P3HT (0.276 W m −1 K −1 ) and 5% for PDPPT (0.420 W m −1 K −1 ) primarily due to the enhanced degree of crystallinity. This work further facilitates the rational design of future organic thermoelectric materials by optimizing the thermal conductivity using controlled doping. The thermal conductivity for CP was enhanced with 5 wt% dopants but impaired with more than 20 wt% dopants. The enhanced thermal conductivity was attributed to higher rDOC and stronger π-π interactions due to small amount of active dopants.